1998
DOI: 10.1039/a706235d
|View full text |Cite
|
Sign up to set email alerts
|

Higher-spin pi multiradical sites in doped polyarylamine polymers

Abstract: P-Doping of conjugated polymers based on an extended m-phenylenediamine motif produces a disperse population of ferromagnetically coupled spin clusters. To increase the average size of these spin clusters variations have been explored both in the structure of the polymer and in the method of doping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…1996(Bushby et al . , 1997aBushby & Gooding 1998) but we have subsequently shown that these problems can be overcome (Bushby et al . 1999).…”
Section: Doping Of the Polymersmentioning
confidence: 98%
See 3 more Smart Citations
“…1996(Bushby et al . , 1997aBushby & Gooding 1998) but we have subsequently shown that these problems can be overcome (Bushby et al . 1999).…”
Section: Doping Of the Polymersmentioning
confidence: 98%
“…The synthetic routes employed are summarized in figures 5 and 6 together with those of model compounds 14 and 23 which contain the essential chromophores/electrophores of the undoped polymers. The synthesis of polymer 15 has been described previously (Bushby & Gooding 1998) and details for the synthesis of polymer 22 are given in the experimental section. The choice of systems 18-22 with two methoxy substituents was dictated by the fact that the synthesis of 'parent' systems (without the methoxy groups) failed because of the poor solubility of the corresponding tetrabromide and intermediates in the synthesis of systems with four methoxy substituents were found to be highly photolabile.…”
Section: Synthesis and Characterization Of The Polymersmentioning
confidence: 99%
See 2 more Smart Citations
“…[20][21][22][23][24][25][26][27][28][29][30] In past decades, although significant progress has been made in the preparation of -conjugated oligomers and polymers with large values of spin quantum number S, organic polymer magnets have remained elusive, in particular, the spin quantum number S is less than 4. 31,32 The structural defects in these polymers can break the radical coupling paths and reduce the whole system into weakly coupled smaller groups, each with a very small magnetic moment. Nevertheless, it should be stressed that a breakthrough work on experiment is achieved by Rajca et al, 33,34 who successfully synthesized a series of polyarylmethyl polymers with very large magnetic moments ͑spin quantum number S can be as high as 5000͒.…”
Section: Introductionmentioning
confidence: 99%